Electrically Controlled Rotor Blade Vortex Interaction Airloads and Noise Analysis Using Viscous Vortex Particle Method - Taoyong Su; Yang Lu; Jinchao Ma; Shujun Guan (Shock and Vibration)
An electrically controlled rotor (ECR), also called a swashplateless rotor, replaces a swashplate with a trailing-edge flap system to implement primary rotor control. To investigate the aerodynamic characteristics of an ECR in blade-vortex interaction (BVI) condition, an analysis model based on the viscous vortex particle method, ECR blade pitch equation, and the Weissinger-L lifting surface model is established. In this model, the ECR wake flow field vorticity is discretized as multiple vortex particles, and the vorticity-velocity form of the Navier-Stokes equation is solved to simulate the transport diffusion of the vorticity. The flap motion-inducing blade-pitch movement is obtained by solving the ECR blade-pitch movement equation via the Runge–Kutta fourth-order method. On the basis, BVI noise radiation of an ECR is evaluated using the Ffowcs Williams and Hawkings (FW-H) equation. Based on the present prediction model, the aerodynamic and acoustic characteristics of a sample ECR in BVI condition are analyzed. The results show that since the BVI event of the ECR on the advancing side is mainly caused by the interaction between the flap tip vortex and the blade, the blade spanwise range of ECR BVI occurrence on the advancing side is smaller than that of the conventional rotor. In addition, the magnitude of the maximum sound pressure level on the advancing side as well as on the retreating side of the ECR is also different from that of the conventional rotor, which is consistent with the difference in the airloads between the ECR and conventional rotor. Furthermore, a study was performed to examine the effect of the pre-index angle on the BVI-induced airloads and noise. The amplitude of the impulsive airloads of the ECR on the advancing side is increased with the increase in pre-index angle, while the amplitude of the impulsive airloads of the ECR on the retreating side is decreased. Indeed, when the pre-index angle of the sample ECR is 8 degrees, the retreating-side noise radiation lobe is almost disappeared. In addition, the different intensity of wake vorticity is the main reason for the differences of the BVI-induced airloads and noise among the ECR with different pre-index angles.